2022
DOI: 10.1093/ofid/ofac706
|View full text |Cite
|
Sign up to set email alerts
|

Can the Future of ID Escape the Inertial Dogma of Its Past? The Exemplars of Shorter Is Better and Oral Is the New IV

Abstract: Like all fields of medicine, Infectious Diseases is rife with dogma that underpins much clinical practice. Here we discuss two specific examples of historical practice that have been overturned recently by numerous prospective studies: traditional durations of antimicrobial therapy and the necessity of intravenous (IV)-only therapy for specific infectious syndromes. These dogmas are based on uncontrolled case series from >50 years ago, amplified by the opinions of eminent experts. Conversely, more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 147 publications
0
21
0
Order By: Relevance
“…To further analyze if DC could have selected other mutations, leading to crossresistance to other antibiotics, we measured MICs to antibiotics from other structural families (ceftazidime, imipenem, aztreonam, fosfomycin, tetracycline, and erythromycin) in the populations grown during 4 days in presence of DC, finding no differences respect to the parental strains (Supplementary Table 3). Finally, and although we propose a therapeutic strategy based on a short treatment (3 days; around 20 generations), as we and others have suggested before 28,29,50,74,75 , we analyzed the capacity of DC to select for ciprofloxacin or tobramycin resistance in the long term (15 days; around 100 bacterial generations). We found that this compound did not lead to an increase of ciprofloxacin or tobramycin MICs in the different genetic backgrounds of P. aeruginosa analyzed (Supplementary Table 4) and that, importantly, the capacity of DC to induce transient CS to tobramycin was preserved (Supplementary Table 5).…”
Section: Dequalinium Chloride Induction Of Cs Is Robust and Specific ...mentioning
confidence: 99%
“…To further analyze if DC could have selected other mutations, leading to crossresistance to other antibiotics, we measured MICs to antibiotics from other structural families (ceftazidime, imipenem, aztreonam, fosfomycin, tetracycline, and erythromycin) in the populations grown during 4 days in presence of DC, finding no differences respect to the parental strains (Supplementary Table 3). Finally, and although we propose a therapeutic strategy based on a short treatment (3 days; around 20 generations), as we and others have suggested before 28,29,50,74,75 , we analyzed the capacity of DC to select for ciprofloxacin or tobramycin resistance in the long term (15 days; around 100 bacterial generations). We found that this compound did not lead to an increase of ciprofloxacin or tobramycin MICs in the different genetic backgrounds of P. aeruginosa analyzed (Supplementary Table 4) and that, importantly, the capacity of DC to induce transient CS to tobramycin was preserved (Supplementary Table 5).…”
Section: Dequalinium Chloride Induction Of Cs Is Robust and Specific ...mentioning
confidence: 99%
“…For example, infectious diseases experts from 4 countries met on Twitter and collaborated to coauthor a paper on the antibiotic topic “Shorter is better and oral is the new IV.” The paper was subsequently posted on Twitter and received 88,900 views in 23 hours. 7 …”
Section: Our Suggestions On How To Get Startedmentioning
confidence: 99%
“…This forced me to critically examine existing data. Namely, we now have 21 RCTs demonstrating that oral therapy is at least as effective and safer for these infections than is IV-only therapy—there are no contrary data . I then reexamined my own practices, challenged the preconceived notions and years of dogma that make up the current guidelines, and, most important, pivoted.…”
Section: Dr Badenmentioning
confidence: 99%
“…Not all patients may be appropriate for oral antibiotic therapy, and reasonable selection criteria have been proposed . Specifically, the patient:…”
Section: Dr Badenmentioning
confidence: 99%